Pulse wave velocity in arterial hypertension patients - O. A. Nazarova; F. Yu. Fomin; O. M. Maslennikova; E. A. Shutemova; A. M. Berezina; O. A. Vasilyeva; M. V. Kelesh (Кардиоваскулярная терапия и профилактика, 2007)
Aim. To study pulse wave velocity (PWV) disturbance prevalence in arterial hypertension (AH) patients, to compare PVW to AH, myocardial structure, and autonomous nervous system parameters. Material and methods. The study included 132 Stage I-II AH patients, 66 men and 66 women; mean age 46,9±7,2 years. In all participants, PWV, heart rate variability (HRV) were measured, 24-hour blood pressure monitoring (BPM) and echocardiography were performed. Results. PWV for elastic and muscular type vessels (Ve, Vm) was increased in 41,7% and 58.3% of the patients, respectively. PWV correlated with age, AH duration, HR and some 24-hour BPM parameters. In particular, Vecorrelated with systolic BP load, and Vm - with diastolic BP load in nighttime. PVW was associated with relative left ventricular (LV) wall thickness, LV myocardial mass index. Ve and Vm were linked to sympathetic and parasympathetic reactivity, respectively. Conclusion. PWV increase correlated with LV remodeling signs. PVW assessment could be recommended for better ambulatory diagnostics of target organ damage in AH patients.